PKM SOSIALISASI PENTINGNYA INKLUSI KESADARAN PAJAK YANG TERINTEGRASI PADA MATA KULIAH BAGI MASYARAKAT DI WILAYAH SUMATERA UTARA - Halimatul Maryani; Muhammad Hizbullah; Syahrul Bakti Harahap; Tri Reni Novita; Dani Sintara; Abdul Halim; Adawiyah Nasution; Rahma Nuriasari (LPPI UMN AL WASHLIYAH, 2025)
Development and expansion in Indonesia certainly require maximum funding, and the need for development must be aligned with current and future development needs. While these development needs can be met through various means, all of them are expected to strengthen the state's financial sector, one of which is the tax sector. One of the goals of promoting tax inclusion through this Community Service Program (PKM) activity is to provide insight and knowledge related to taxation information.